Active recovery effects by previously inactive muscles on 40-s exhaustive cycling - Fujita, Y.; Koizumi, K.; Sukeno, S.; Manabe, M.; Nomura, J. (Journal of Sports Sciences, 2009)
The effects of active recovery using previously active and inactive muscle groups on power output and respiratory responses were examined. Ten male volunteers underwent two exhaustive 40-s bouts of leg cycling (1st Ex and 2nd Ex), separated by a 20-min recovery period. The recovery conditions were leg (Leg-Active) or arm (Arm-Active) cranking at 50% ventilatory threshold (VT), or sedentary control (Passive). The total output work (Total work) during the 2nd Ex in the Leg-Active condition was significantly higher than that in the Passive (299 vs. 282 J/kg body mass (J/BM)). The values of Total work, peak O2 and peak heart rate during the 2nd Ex were significantly higher than those during the 1st Ex in both Leg- and Arm-Active. Total CO2excess after the 1st Ex was significantly higher than that after the 2nd Ex (67.6 vs. 26.0 ml · BM-1) in Passive. After the 2nd Ex, the Total CO2excess in the Leg-Active (51.5 ml/BM) was significantly higher than that in both the Passive (26.0) and Arm-Active (36.5), with Arm-Active being significantly higher than Passive. The recovery exercise using previously inactive muscles improved respiratory compensation ability related to performance enhancement.